The Relationship Between Learning Independence and Attitude Toward Science For Junior High School Students - Kurniawan, Dwi Agus; Astalini, Astalini; Darmaji, Darmaji; Destianti, Alfika (FKIP Universitas Lampung, 2019)
The Relationship Between Learning Independence and Attitude Towards Science for Junior High School Students. Objectives: This study aims to determine the relationship between learning independence and student attitudes on science subjects in junior high school. Methods: This research is an associative quantitative research. The instrument used was a questionnaire to obtain science learning independence data. Data collection on science learning independence is done through giving questionnaires to students. Data were analyzed using descriptive statistics. Findings: There are learning independece and four indicators of student attitudes towards science subjects include: (1) social implications for science; (2) attitude towards investigations in science; (3) adoption of scientific attitudes; (4) Enjoyment in learning science. The relationship between learning independence and students’ attitudes on Pearson coefficient 0.657. Conclusions: A significant and positive relationship presented by learning independence and attitudes on science subjects in junior high school. Keywords: Learning independence; student attitudes; natural science subjects, junior high school. DOI: http://dx.doi.org/10.23960/jpp.v9.i2.201901